A Recent Achievement in the Discovery and Development of Vaccines and Therapeutic Agents in the Race for COVID-19 Protection and Treatment - Zemene Demelash Kifle MSc; Engidaw Fentahun Enyew MSc; Abebe Basazn Mekuria MSc (SAGE Publishing, 2021)
Currently, the coronavirus disease 2019 (COVID-19) is a big challenge to the healthcare systems in the world. Several researchers in the world have immediately carried out clinical investigations for the discovery of vaccines and drugs. Different studies have shown that antiviral measures including small bioactive compounds targeting multifaceted molecular communications take in COVID-19 infection. The drug development archived in this review emphasizes mainly on drugs that are effective for the Management of MERS-CoV, SARS-CoV, and other RNA viruses. The investigation of therapeutic agents for COVID-19 includes anti-inflammatory agents, antibodies, and nucleic acid-based treatments targeting virus gene expression as well as different sorts of vaccines. Numerous patents revealed techniques of these biologics with the potential for treating and preventing coronavirus infections, which may apply to COVID-19. Phase 3 clinical trials such as Sputnik V, AZD1222, mRNA-1273, BNT162b2, Ad5-nCoV, Anti-COVID antibodies, Kevzara; Actemra, Jakafi; Baricitinib, and some others were undergoing in the race for Covid-19 treatment. However, there's still a lack of a review on vaccines and drugs for COVID-19 management. Therefore, this review summarizes different studies that are ongoing in the race for Covid-19 protection and treatment.